3D Contractile Responses of Normal and Diseased Human Aortic Valve Interstitial Cells. (9th April 2021) - Khang, Alex; Camillo, Chiara; Ferrari, Giovanni; Sacks, Michael S.
Abstract : Objective : The bicuspid aortic valve (BAV) contains two rather than the normal three leaflets; and is actually a spectrum of structural anomalies that can include a raphe region. For reasons that remain unclear, BAVs calcify faster than normal aortic valves (NAVs). Structural remodeling in BAV is driven by aortic valve interstitial cells (AVICs) that can become activated due to mechanical and biochemical cues. Increased contractility is a hallmark of activation and reflects AVIC biophysical state. In this study, we assessed the 3D contractile responses of AVICs extracted from BAVs and NAVs to develop an improved understanding of their intrinsic function and differences. Methods : AVICs from the raphe and non-raphe regions of human BAVs were assessed. AVICs from human NAVs served as controls. AVICs and fluorescent microbeads were seeded within PEG hydrogels. Image stacks of an AVIC and surrounding fluorescent microbeads were obtained within normal and relaxed (CytochalasinD) conditions. The positions of the beads were tracked between each image stack using a custom software which output local hydrogel displacements (Figure 1A-C ). Results : AVICs from BAVs produced lower levels of hydrogel displacements than NAVs (Figure 1D ). Interestingly, AVICs from the raphe and non-raphe regions produced similar levels of displacements. AVICs produced complex displacement fields with regions of contraction and expansion. Furthermore, contractile displacements occurred at cell pseudopods whereas expansive displacements occurred near the mid-section of the cell. Conclusions : Contractile behaviors differed substantially between BAVs and NAVs, which suggests that AVICs are intrinsically different between the two valve types. This result suggests that AVICs are fundamentally different and that the larger BAV disorder affects the cellular scale as well as the organ-level anatomy, and will lay basis for future cellular-based therapies.